Glucose Metabolism in Acute Kidney Injury and Kidney Repair - Wen, Lu; Li, Ying; Li, Siyao; Hu, Xiaoru; Wei, Qingqing; Dong, Zheng (Frontiers in Medicine, 2021)
The kidneys play an indispensable role in glucose homeostasis via glucose reabsorption, production, and utilization. Conversely, aberrant glucose metabolism is involved in the onset, progression, and prognosis of kidney diseases, including acute kidney injury. In this review, we describe the regulation of glucose homeostasis and related molecular factors in kidneys under normal physiological conditions. Furthermore, we summarize recent investigations about the relationship between glucose metabolism and different types of acute kidney injury. We also analyze the involvement of glucose metabolism in kidney repair after injury, including renal fibrosis. Further research of glucose metabolism in kidney injury and repair may lead to the identification of novel therapeutic targets for the prevention and treatment of kidney diseases.